Quality competition and entry deterrence: When to launch a second brand. (28th June 2017) - Müller, Stephan; Götz, Georg
Abstract : We study the rationale for an incumbent to launch a second brand when facing potential entry into a market with quality‐differentiated products and a fringe producer. Depending on market size, the cost of a second brand and a potential entrant's setup cost the incumbent might use a second brand both when deterring and when accommodating entry. For low costs of brand proliferation, the high‐quality firm will prevent entry with limit qualities or multiple brands. The high‐quality incumbent will accommodate entry only if it cannot be prevented. Accommodation is always accompanied by an additional brand safeguarding the premium brand.